Intraoperative Vagal Excitation During Rigid Esophagoscopy for an Esophageal Earring in a 4-Month-Old Infant: A Case Report - Ilham Daryl Fathurozzi Alamsjah; Ade Asyari; Rio Rusman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Esophageal foreign body ingestion is a prevalent otorhinolaryngologic emergency in the pediatric population but is epidemiologically rare in infants under six months of age. While rigid esophagoscopy remains the gold standard for extraction, it involves stimulating the highly innervated aerodigestive tract. This case highlights a life-threatening vagal reflex—an underreported complication in infants—during foreign body removal. Case presentation: A 4-month-old female infant presented with a history of accidental earring ingestion three days prior, manifesting as hypersalivation and feeding refusal. Radiographic imaging confirmed a radiopaque foreign body at the T1 vertebral level or thoracic inlet. The patient underwent rigid esophagoscopy under general anesthesia. During the extraction phase, mechanical manipulation of the esophageal mucosa triggered profound vagal excitation, resulting in severe bradycardia and oxygen desaturation. The procedure was immediately paused, and the patient was successfully resuscitated using vagolytic agents and hyperoxygenation by the anesthesiology team. A second attempt was successful without recurrence of the reflex. Post-operative recovery was uneventful. Conclusion: Foreign body ingestion in early infancy requires a high index of suspicion and meticulous perioperative planning. The manipulation of the esophageal inlet can trigger potent vagovagal reflexes, particularly in infants with high vagal tone. This case underscores the necessity of deep anesthetic planes, prophylactic vagolytic preparation, and seamless communication between the surgeon and anesthesiologist to manage hemodynamic instability.